Quantifying the functional rehabilitation of injured football players - Fuller, C. W.; Walker, J. (British Journal of Sports Medicine, 2006)
Objective: To determine whether quantified, auditable records of functional rehabilitation can be generated using subjective assessments of players` performance in fitness tests routinely used in professional football.